♧ Brainly Stars
♧ Moderators
♧ Other Users
ㅤ
![\Large{\underline{\underline{\pink{\bf{ \bigstar \: \: Question :-}}}}} \Large{\underline{\underline{\pink{\bf{ \bigstar \: \: Question :-}}}}}](https://tex.z-dn.net/?f=%5CLarge%7B%5Cunderline%7B%5Cunderline%7B%5Cpink%7B%5Cbf%7B+%5Cbigstar+%5C%3A+%5C%3A+Question+%3A-%7D%7D%7D%7D%7D)
Simplify and express each as a rational number :
(i) ![\sf\large \bigg(\frac{4}{9}\bigg)^6 \: \times \: \sf\large \bigg(\frac{4}{9}\bigg)^{-4} \sf\large \bigg(\frac{4}{9}\bigg)^6 \: \times \: \sf\large \bigg(\frac{4}{9}\bigg)^{-4}](https://tex.z-dn.net/?f=%5Csf%5Clarge+%5Cbigg%28%5Cfrac%7B4%7D%7B9%7D%5Cbigg%29%5E6+%5C%3A+%5Ctimes+%5C%3A+%5Csf%5Clarge+%5Cbigg%28%5Cfrac%7B4%7D%7B9%7D%5Cbigg%29%5E%7B-4%7D+)
(ii) ![\sf\large \bigg(\frac{-7}{8}\bigg)^{-3} \: \times \: \sf\large \bigg(\frac{-7}{8}\bigg)^{2} \sf\large \bigg(\frac{-7}{8}\bigg)^{-3} \: \times \: \sf\large \bigg(\frac{-7}{8}\bigg)^{2}](https://tex.z-dn.net/?f=%5Csf%5Clarge+%5Cbigg%28%5Cfrac%7B-7%7D%7B8%7D%5Cbigg%29%5E%7B-3%7D+%5C%3A+%5Ctimes+%5C%3A+%5Csf%5Clarge+%5Cbigg%28%5Cfrac%7B-7%7D%7B8%7D%5Cbigg%29%5E%7B2%7D+)
(iii) ![\sf\large \bigg(\frac{4}{3}\bigg)^{-3} \: \times \: \sf\large \bigg(\frac{4}{3}\bigg)^{-2} \sf\large \bigg(\frac{4}{3}\bigg)^{-3} \: \times \: \sf\large \bigg(\frac{4}{3}\bigg)^{-2}](https://tex.z-dn.net/?f=%5Csf%5Clarge+%5Cbigg%28%5Cfrac%7B4%7D%7B3%7D%5Cbigg%29%5E%7B-3%7D+%5C%3A+%5Ctimes+%5C%3A+%5Csf%5Clarge+%5Cbigg%28%5Cfrac%7B4%7D%7B3%7D%5Cbigg%29%5E%7B-2%7D+)
Answers
Answered by
63
Answer:
(i) 16/81
(ii) 8/7
(iii) 243/1024
Step-by-step explanation:
I am not using LaTeX to save time. Sorry for the inconveniences !
(i) (4/9)⁶ × (4/9)⁻⁴
= 4⁶/9⁶ × (9/4)⁴
= 4⁶/9⁶ × 9⁴/4⁴
= 4⁶⁻⁴ × 9⁴⁻⁶
= 4² × 9⁻²
= 4²/9²
= 16/81
(ii) (-7/8)⁻³ × (-7/8)²
= (8/-7)³ × (-7/8)²
= 8³/-7³ × -7²/8²
= 8³⁻² × -7²⁻³
= 8 × -7⁻¹
= 8/7
(iii) (4/3)⁻³ × (4/3)⁻²
= (3/4)³ × (3/4)²
= 3³/4³ × 3²/4²
= 3³⁺²/4³⁺²
= 3⁵/4⁵
= (3/4)⁵
= 243/1024
LAWS OF EXPONENT :
- aᵐ × aⁿ = aᵐ ⁺ ⁿ
- aᵐ ÷ aⁿ = aᵐ ⁻ ⁿ
- a⁻ᵐ = 1/aᵐ
- a⁻¹ = 1/a
- (ab)ᵐ = aᵐ × bᵐ
- (a/b)ᵐ = aᵐ / bᵐ
- a⁰ = 1
Thanks !
Answered by
38
QUESTION :- Simplify and express each as a rational number :-
1•}
2•}
3•}
Similar questions